Development of Teaching Materials for Writing Argumentative-Based on Lotus Teacniques on grade XII Madrasah Aliyah Negeri - Rika Rani; Resdin Purba; Risnawaty Risnawaty (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
This study aims to describe the development of teaching material patterns, the feasibility of teaching materials, and the effectiveness of teaching materials in writing paragraphs of argumentation based on lotus techniques in class XII MAN Pematangsiantar. Kind of this research is research and development based on the model of Borg and Gall. Subject trials consist of subject experts, design experts. The results showed that: (1) validation of the content experts include the freasibility of content with an average of 82,35 in very good criteria, eligibility presentation with an average of 86,545 in the very well criteria, aspects of language with an average of 90,38% in the very well criteria, (2) validation of design experts with an average of 85,00% in the very well criteria, (3) individual testing with an average of 82,87% with a very good criteria, (4) the trial of small group with an average of 91,20% with a very good criteria, and (5) a limited field test groups with an average of 95,10% with a very good criteria, (6) the effectiveness of instructional materials with a presentation by 74,22% with good criteria. Thus, the instructional materials of argumentative paragraph based on lotus tehnic that have been developed is proper to use in the learning process as a learning resource. Keywords: Intructional naterials, argumentative paragraph, lotus tehnic based Abstrak Penelitian ini bertujuan untuk mendeskripsikan pengembangan pola bahan ajar, kelayakan bahan ajar, dan keefektifan bahan ajar menulis paragraf argumentasi berbasis teknik teratai pada siswa kelas XII MAN Pematangsiantar. Penelitian pengembangan ini mengacu pada model Borg and Gall, yang terdiri atas materi, desain, uji coba. Data dikumpulkan melalui angket. Hasil penelitian menunjukkan bahwa: (1) validasi ahli materi kelayakan isi dengan rata-rata 82,35 pada kriteria sangat baik, kelayakan penyajian dengan rata-rata 86,54% pada kriteria sangat baik, aspek bahasa dengan rata-rata 90,38% pada kriteria sangat baik, (2) validasi ahli desain dengan rata-rata 85,00% pada kriteria sangat baik, (3) uji coba perorangan dengan rata-rata 82,87% dengan kriteria sangat baik, (4) uji coba kelompok kecil dengan rata-rata 91,20% dengan kriteria sangat baik, dan (5) uji kelompok lapangan terbatas dengan rata-rata 95,10% dengan kriteria sangat baik, (6) keefektifan bahan ajar dengan presentasi 74,22% dengan kriteria baik. Dengan demikian, bahan ajar paragraf argumentasi berbasis teknik teratai yang telah dikembangkan layak untuk digunakan dalam proses pembelajaran sebagai sumber belajar. Kata kunci: bahan ajar, paragraf argumentasi, berbasis teknik teratai